Validity and Reliability of Agoraphobic Cognitions Questionnaire-Turkish Version - Ayşegül KART; M. Hakan TÜRKÇAPAR (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Validity and Reliability of Agoraphobic Cognitions Questionnaire-Turkish Version Objective: The aim of this study is to investigate the validity and reliability of Agoraphobic Cognitions Questionnaire -Turkish Version (ACQ). Method: ACQ was administered to 92 patients with agoraphobia or panic disorder with agoraphobia. BSQ Turkish version completed by translation, back-translation and pilot assessment. Reliability of ACQ was analyzed by test-retest correlation, split-half technique, Cronbach’s alpha coefficient. Construct validity was evaluated by factor analysis after the Kaiser-Meyer-Olkin (KMO) and Bartlett test had been performed. Principal component analysis and varimax rotation used for factor analysis. Results: 64% of patients evaluated in the study were female and 36% were male. Age interval was between 18 and 58, mean age was 31.5±10.4. The Cronbach’s alpha coefficient was 0.91. Analysis of test-retest evaluations revealed that there were statistically significant correlations ranging between 24% and 84% concerning questionnaire components. In analysis performed by split-half method reliability coefficients of half questionnaires were found as 0.77 and 0.91. Again Spearmen-Brown coefficient was found as 0.87 by the same analysis. To assess construct validity of ACQ, factor analysis was performed and two basic factors found. These two factors explained 57.6% of the total variance. (Factor 1: 34.6%, Factor 2: 23%) Conclusion: Our findings support that ACQ-Turkish version had a satisfactory level of reliability and validity